Received Opinions: Doxography in Antiquity and the Islamic World - Lammer, Andreas,; Jas, Mareike, (Philosophia Antiqua ;, 2022)
This volume-the proceedings of a 2018 conference at LMU Munich funded by the Fritz Thyssen Foundation-brings together, for the first time, experts on Greek, Syriac, and Arabic traditions of doxography. Fourteen contributions provide new insight into state-of-the-art contemporary research on the widespread phenomenon of doxography. Together, they demonstrate how Greek, Syriac, and Arabic forms of doxography share common features and raise related questions that benefit interdisciplinary exchange among colleagues from various disciplines, such as classics, Arabic studies, and the history of philosophy.